Symposium 1: Curate me! Exploring online identity through social curation in networked learning - Seitzinger, Joyce (Proceedings of the International Conference on Networked Learning, 2014)
Networked learning theory and the related literature express the importance of access to resources or content, but there is no singular way of discussing these information management processes. On the web, the rise in information abundance has seen the terms curation, digital curation, content curation, and social curation gain in popularity to describe how individual users manage their information intake, processing and sharing. This paper attempts to distinguish between these overlapping terms and argues that the term social curation could describe the information management processes required of networked educators and learners. In addition it proposes a terminology for phases of the social curation process, which may aid networked learners and educators in the adoption and scaffolding of social curation processes for learning. This paper further explores the distinctive opportunities social curation offers for online identity expression and construction for circumventing known issues such as collapsed contexts and role conflict that occur in other social media sites.